Ancestral Exposure to Stress Generates New Behavioral Traits and a Functional Hemispheric Dominance Shift. (10th March 2016) - Ambeskovic, Mirela; Soltanpour, Nasrin; Falkenberg, Erin A.; Zucchi, Fabiola C.R.; Kolb, Bryan; Metz, Gerlinde A.S.
Abstract: In a continuously stressful environment, the effects of recurrent prenatal stress (PS) accumulate across generations and generate new behavioral traits in the absence of genetic variation. Here, we investigated if PS or multigenerational PS across 4 generations differentially affect behavioral traits, laterality, and hemispheric dominance in male and female rats. Using skilled reaching and skilled walking tasks, 3 findings support the formation of new behavioral traits and shifted laterality by multigenerational stress. First, while PS in the F1 generation did not alter paw preference, multigenerational stress in the F4 generation shifted paw preference to favor left-handedness only in males. Second, multigenerational stress impaired skilled reaching and skilled walking movement abilities in males, while improving these abilities in females beyond the levels of controls. Third, the shift toward left-handedness in multigenerationally stressed males was accompanied by increased dendritic complexity and greater spine density in the right parietal cortex. Thus, cumulative multigenerational stress generates sexually dimorphic left-handedness and dominance shift toward the right hemisphere in males. These findings explain the origins of apparently heritable behavioral traits and handedness in the absence of DNA sequence variations while proposing epigenetic mechanisms.